High-purity allylamine (co)polymer and method for producing the same
By controlling the ratio of sulfuric acid groups in allylamine (co)polymer and decomposition and purification, the coloring and impurity problems of allylamine (co)polymer in the prior art are solved, and low coloring, low impurity and long-term stability are achieved polymer preparation.
Patent Information
- Application Number
- CN202310208628.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-07-05
- Filing Date
- 2018-06-19
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2038-06-19
AI Technical Summary
The prior art is difficult to prepare allylamine (co)polymers with low coloring, low impurities and long-term stability, especially the problems of increasing the time and generation of impurities such as sulfuric acid are difficult to solve.
By controlling the proportion of sulfuric acid groups in the polymer structure, it is ensured to be less than 20,000 mass ppm, thereby inhibiting the generation of sulfuric acid and deepening of coloring. The sulfuric acid groups are decomposed by heating, oxidizing or hydrolysis, and removed by refining treatment such as distillation and electrodialysis. Impurities.
It has achieved the reduction of coloring and impurities to extremely low levels, and can maintain these excellent characteristics for a long time. It is suitable for electrical and electronic materials, papermaking treatment agents, inks, coatings and other fields.
Smart Images

Figure QLYQS_1 
Figure BDA0004111769050000041 
Figure BDA0004111769050000191
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with application number 201880043142.2, application date June 19, 2018, and invention name “High-purity allylamine (co)polymer and its production method”. Technical Field
[0002] The present invention relates to a method for producing a high-purity allylamine (co)polymer. More specifically, the present invention relates to a high-purity allylamine (co)polymer that prevents coloration and effectively suppresses the increase of coloration and the generation of impurities over time and a method for producing the same. Background Art
[0003] It is generally known that allylamine is difficult to polymerize due to destructive chain transfer, and an effective method for producing allylamine polymers has become a research object. As a method proposed in the past, it is known that a method for synthesizing allylamine addition salts using azo-based free radical initiators in polar solvents (refer to patent document 1, patent document 2). In addition, it is known that a method for synthesizing low-molecular-weight allylamine polymers using a large amount of peroxide-based free radical initiators (refer to patent document 3).
[0004] However, the low molecular weight allylamine polymer obtained by the above method is colored brown due to the synthesis under a large amount of peroxide-based free radical initiator and severe temperature conditions, and has a large amount of scorching residue from the initiator. In addition, the polymer has the following problem: its coloration tends to deepen over time.
[0005] As a method for improving this, a method is known in which unreacted allylamine in the low molecular weight allylamine polymer obtained by the above method is removed by distillation and the generated salt is removed by purification to reduce coloration and the amount of ignition residue (see Patent Document 4).
[0006] However, even when the low molecular weight allylamine polymer obtained by the above method is used in the field of electronic materials, there are still concerns about its coloration and growth over time, especially growth over time at high temperatures and growth over time of impurities such as sulfuric acid, and there is a strong demand for allylamine (co)polymers with higher purity and further suppressed coloration and growth.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 58-201811
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 62-172007
[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 5-195450
[0012] Patent Document 4: International Publication No. 99 / 19372A1 Pamphlet Summary of the invention
[0013] Problems to be solved by the invention
[0014] The present invention has been made in view of the above-mentioned background technology, and can meet the requirements for prevention of coloration, long-term stability and low impurities even when used in electronic materials, display materials, inks and other applications. The subject is to provide an allylamine (co)polymer having low coloration, low impurities and excellent long-term stability and a method for producing the same, beyond the limits of the prior art.
[0015] Means for solving problems
[0016] The present inventors have conducted intensive studies to achieve the above-mentioned object and have found that an allylamine (co)polymer having a sulfate group ratio in the polymer structure of a specific value or less can solve the above-mentioned problems, thereby completing the present invention.
[0017] That is, the present invention and its various aspects are as described in the following [1] to
[12] .
[0018] [1] An allylamine (co)polymer having a structural unit derived from allylamine, wherein the structure contains sulfuric acid groups, and the ratio of the sulfuric acid groups to the total mass of the allylamine (co)polymer is less than 20,000 ppm by mass.
[0019] [2] The allylamine (co)polymer described in [1], wherein the ratio of the sulfate group to the total mass of the allylamine (co)polymer is 15000 ppm by mass or less.
[0020] [3] The allylamine (co)polymer described in [1] or [2], wherein the weight average molecular weight is 250 to 2500.
[0021] [4] The allylamine (co)polymer according to any one of [1] to [3], wherein the initial absorbance A at a wavelength of 510 nm measured in an aqueous solution of the allylamine (co)polymer prepared to have a concentration of 10% by mass and a pH of 11 is 510 The absorbance A' at a wavelength of 510 nm after the aqueous solution was kept at 70°C for 2 days was 0.5 or less. 510 and initial absorbance A 510 Ratio A' 510 / A510 Is 3 or less.
[0022] [5] The allylamine (co)polymer according to any one of [1] to [4], wherein the proportion of the structural units derived from allylamine in all the structural units is 10 mol% or more.
[0023] [6] A method for producing an allylamine (co)polymer, comprising:
[0024] a) polymerizing the allylamine monomer to obtain an allylamine (co)polymer,
[0025] b) a step of decomposing the sulfuric acid groups in the obtained allylamine (co)polymer, and
[0026] c) A step of removing sulfur compounds generated by decomposition of sulfuric acid groups.
[0027] [7] The method for producing an allylamine (co)polymer described in [6], wherein, in the step b), the amount of sulfate groups in the allylamine (co)polymer is reduced to less than 20,000 ppm by mass relative to the total mass of the allylamine (co)polymer.
[0028] [8] The method for producing an allylamine (co)polymer described in [6], wherein, in the step b), the amount of sulfate groups in the allylamine (co)polymer is reduced to less than 15000 ppm by mass relative to the total mass of the allylamine (co)polymer.
[0029] [9] The method for producing an allylamine (co)polymer according to any one of [6] to [8], wherein in the step b), the allylamine (co)polymer obtained in the step a) is heated at a temperature of 70° C. or higher for 12 hours or more.
[0030]
[10] A paper treatment agent, ink, coating or adhesive containing the allylamine (co)polymer described in any one of [1] to [5].
[0031]
[11] An electrical and electronic material or a display material comprising the allylamine (co)polymer described in any one of [1] to [5].
[0032]
[12] A light-transmitting material comprising the allylamine (co)polymer described in any one of [1] to [5].
[0033] Effects of the Invention
[0034] The allylamine (co)polymer of the present invention achieves a remarkable technical effect beyond the limits of the prior art in that coloration and impurities are reduced to extremely low levels and these preferred properties can be maintained for a long time, and can be suitably used in various applications requiring low coloration and low pollution, represented by electrical and electronic materials, papermaking treatment agents, inks, coatings, adhesives, display materials, and light-transmitting materials.
[0035] According to the production method as another embodiment of the present invention, an allylamine (co)polymer having preferred characteristics, represented by the above-mentioned allylamine (co)polymer, can be efficiently produced. DETAILED DESCRIPTION
[0036] Allylamine (co)polymer
[0037] The present invention is an allylamine (co)polymer having a structural unit derived from allylamine, containing a sulfate group in the structure, and the ratio of the sulfate group to the total mass of the allylamine (co)polymer is 20000 mass ppm or less.
[0038] That is, the allylamine (co)polymer of the present invention only needs to have a structural unit derived from an allylamine monomer, and may be a copolymer (copolymer) having other structural units at the same time, or may be a so-called homopolymer having no other structural units.
[0039] In addition, the allylamine (co)polymer of the present invention contains a sulfate group in a prescribed amount or less in its structure. The sulfate group is introduced into the structure due to the peroxide-based free radical initiator usually used in polymerization, and there are also cases where the sulfate group is introduced into the structure due to other reasons, and such sulfate groups are also included, and the total amount of the sulfate groups needs to be below the prescribed value.
[0040] Structural units derived from allylamine
[0041] The essential structural unit of the allylamine (co)polymer of the present invention, ie, the structural unit derived from the allylamine monomer, has a structure represented by the following formula (I).
[0042] [Chemistry 1]
[0043]
[0044] Among them, the structural unit derived from the monoallylamine monomer only needs to have a structure represented by the above formula (I), and it is not actually necessary to be a structure obtained by polymerizing monoallylamine. For example, an addition salt of monoallylamine can be used as a raw material monomer. The addition salt of monoallylamine used at this time is usually an inorganic acid salt of monoallylamine. Examples of such inorganic acid salts of monoallylamine include hydrochloride, sulfate, phosphate, perchlorate, nitrate, etc. of monoallylamine. From the perspective of ease of acquisition, hydrochloride is preferably used. In addition, organic acid salts such as acetate can also be used.
[0045] Structural units other than structural units derived from allylamine
[0046] When the allylamine (co)polymer of the present invention is a copolymer, there is no particular limitation on the structural units other than the structural unit derived from allylamine, and such structural units can be derived by copolymerizing with appropriately using a monomer copolymerizable with allylamine.
[0047] Preferred examples of copolymerizable monomers include monoallylamines such as methylallylamine and dimethylallylamine or their addition salts; diallylamines such as diallylmethylamine or their addition salts; diallyldialkylammonium salts such as diallyldimethylammonium chloride; acrylamide, dimethylacrylamide, acryloylmorpholine, N-[3-(dimethylamino)propyl](meth)acrylamide, (3-acrylamidopropyl)trimethylammonium chloride, (3 -methacrylamides such as (2-methacrylamidopropyl)trimethylammonium chloride; allyl alcohols, allyl ethers such as ethylene glycol monoallyl ether, unsaturated carboxylic acids such as (sodium) (meth)acrylic acid or their addition salts; unsaturated dicarboxylic acids such as maleic acid and fumaric acid or their salts; sulfur dioxide; allyl sulfonic acids such as (sodium) (meth)allyl sulfonic acid or their addition salts; vinyl sulfonic acids such as (sodium) vinyl sulfonic acid or their addition salts; sodium isoprene sulfonate, etc., but are not limited to these.
[0048] The monomers other than allylamine may be used alone or in combination of two or more.
[0049] Sulfate
[0050] Furthermore, the allylamine (co)polymer of the present invention contains a sulfate group in its structure, and the ratio of the sulfate group to the total mass of the allylamine (co)polymer is 20000 mass ppm or less.
[0051] The sulfate group is usually introduced into the structure by a peroxide-based free radical initiator such as sodium persulfate used during polymerization, but may also be introduced into the structure by other reasons. In addition, the allylamine (co)polymer of the present invention is usually polymerized using a peroxide-based free radical initiator.
[0052] In the allylamine (co)polymer of the present invention, regardless of its origin, the total amount of sulfate groups contained in the structure thereof needs to be 20,000 mass ppm or less relative to the total mass of the allylamine (co)polymer.
[0053] To date, in order to suppress the coloration of allylamine (co)polymers and remove impurities, unreacted allylamine has been distilled off, and allylamine (co)polymers have been purified by electrodialysis or acid treatment. However, even after these treatments, coloration increases over time and sulfur-containing impurities are sometimes generated, and it is hoped that these problems can be solved. The inventors have found that these coloration increases and impurity generation are caused by sulfate groups covalently bonded to polymer chains, and more specifically, sulfuric acid generated by the hydrolysis of such sulfate groups over time also leads to coloration increases over time and the generation of sulfur-containing impurities.
[0054] As mentioned above, sulfate group is usually from the peroxide-based free radical initiators such as sodium persulfate used during polymerization and is introduced into the structure. Especially, peroxide-based free radical initiators are due to strong free radical activity, therefore sometimes not only make sulfate group and the polymer end bonding of allylamine (to) polymer, but also make sulfate group and polymer chain bonding. Even if the sulfate group covalently bonded to the polymer chain can not be fully removed by refining treatments such as distillation, electrodialysis, acid treatment, it is inferred that therefore existing technology fails to fully solve the problem of coloring increase over time, the generation of sulfur-containing impurities.
[0055] The present invention achieves the remarkable technical effects of being able to suppress the production of sulfuric acid caused by the decomposition of sulfate groups to a level that is not a practical problem, and being able to effectively suppress coloration and impurity production for a long time by limiting the ratio of sulfate groups bonded in the structure of the allylamine (co)polymer to less than 20,000 mass ppm relative to the total mass of the allylamine (co)polymer.
[0056] The ratio of the sulfuric acid group bonded in the structure of the allylamine (co)polymer of the present invention is preferably 18000 mass ppm or less, more preferably 15000 mass ppm or less, relative to the total mass of the allylamine (co)polymer.
[0057] The lower the proportion of bonded sulfate groups in the structure of the allylamine (co)polymer of the present invention, the more preferred it is, and there is no particular lower limit. In the case where a certain level of sulfate groups is temporarily introduced into the structure due to a free radical initiator, etc., if the sulfate groups are reduced at the usual cost and time, in most cases it becomes more than 10 mass ppm.
[0058] The ratio of the sulfuric acid group bonded to the structure of the allylamine (co)polymer can be measured by, for example, the following method.
[0059] Ion exchange water is appropriately added to the aqueous solution of the allylamine (co)polymer to adjust its concentration and pH to a range suitable for the measurement, for example, about 10% by mass and pH 11. The solution is used to measure the sulfur concentration by an ion chromatograph with a combustion device. The ratio of the sulfate group in the polymer (mass basis) is calculated from the obtained sulfur concentration, the amount of the solution, and the concentration of the allylamine (co)polymer in the solution, taking into account the molecular weight of the sulfate group and the atomic weight of sulfur.
[0060] Examples of means for appropriately adjusting the proportion of sulfate groups bonded in the structure of the allylamine (co)polymer include decomposing the sulfate groups bonded in the structure by heating, etc.; oxidative decomposition using an oxidant, a catalyst, etc.; hydrolysis using an acid, an alkali, electromagnetic waves, ultrasonic waves, etc., etc.
[0061] When decomposition is performed by heating, the obtained allylamine (co)polymer is preferably heated at a temperature of 70° C. or higher for 12 hours or longer in the state of an aqueous solution, but the conditions for decomposition by heating are not limited thereto.
[0062] In order to suppress initial coloration and impurities, it is desirable to remove sulfur compounds generated by decomposition of sulfuric acid groups in the above-mentioned heating treatment, etc. There is no particular limitation on the method for removing sulfur compounds, and distillation, electrodialysis, acid treatment, etc. used in conventional purification treatments can be used.
[0063] As described above, in the present invention, by limiting the ratio of the sulfuric acid groups bonded in the structure of the allylamine (co)polymer to the total mass of the allylamine (co)polymer to less than 20,000 ppm by mass, a significant technical effect of being able to effectively suppress coloration for a long time is achieved.
[0064] More specifically, the initial absorbance A at a wavelength of 510 nm measured in an aqueous solution of the allylamine (co)polymer of the present invention adjusted to a concentration of 10 mass % and a pH of 11 is: 510 Preferably, it is 0.5 or less. In addition, the initial absorbance A at a wavelength of 510 nm measured in an aqueous solution of the allylamine (co)polymer of the present invention adjusted to a concentration of 10 mass % and a pH of 11 is 510 The absorbance A' at a wavelength of 510 nm after the allylamine (co)polymer aqueous solution was kept at 70°C for 2 days 510 Ratio A' 510 / A 510 It is preferably 3 or less. More preferably, the allylamine (co)polymer of the present invention satisfies these conditions simultaneously.
[0065] The initial absorbance A of the allylamine (co)polymer of the above preferred embodiment is 510When the ratio is 0.5 or less, coloration is effectively suppressed, and thus the polyurethane can be suitably used in various applications where suppression of coloration is important, such as paper processing agents, inks, coatings, display-related materials, and transmissive materials.
[0066] In addition, the allylamine (co)polymer of the preferred embodiment described above is measured by the absorbance A at a wavelength of 510 nm measured for an aqueous solution of the allylamine (co)polymer adjusted to a concentration of 10 mass % and a pH of 11. 510 The absorbance A' at a wavelength of 510 nm after the allylamine (co)polymer aqueous solution was kept at 70°C for 2 days 510 Ratio A' 510 / A 510 When the ratio is 3 or less, coloration is effectively suppressed for a long period of time, and thus the material can be suitably used for a long period of time in the above-mentioned applications where suppression of coloration is important, which greatly contributes to the improvement of its life and long-term reliability.
[0067] The initial absorbance A at a wavelength of 510 nm measured in an aqueous solution adjusted to a concentration of 10 mass % and a pH of 11 of the allylamine (co)polymer of the preferred embodiment described above is 510 It is more preferably 0.3 or less, and particularly preferably 0.2 or less.
[0068] The initial absorbance A at a wavelength of 510 nm of the allylamine (co)polymer of the above preferred embodiment is 510 The absorbance A' at a wavelength of 510 nm after the allylamine (co)polymer aqueous solution was kept at 70°C for 2 days 510 Ratio A' 510 / A 510 It is more preferably 2.5 or less, and particularly preferably 2 or less.
[0069] The absorbance of the allylamine (co)polymer at a wavelength of 510 nm can be measured, for example, by appropriately adding ion exchange water to an aqueous solution of the allylamine (co)polymer, adjusting the concentration to about 10% by mass and the pH to about 11, injecting the solution into a cell with an optical path length of 10 mm, and measuring it with a spectrophotometer.
[0070] The initial absorbance A at a wavelength of 510 nm measured for an aqueous solution of the allylamine (co)polymer adjusted to a concentration of 10 mass % and a pH of 11 510 and initial absorbance A 510 The absorbance A' of the allylamine (co)polymer aqueous solution after being kept at 70°C for 2 days 510 Ratio A' 510 / A 510All of them can be reduced by reducing the amount of sulfuric acid groups bonded in the structure of the allylamine (co)polymer. The method for reducing the amount of sulfuric acid groups bonded in the structure of the allylamine (co)polymer is as described above.
[0071] The molecular weight of the allylamine (co)polymer of the present invention is not particularly limited, and a (co)polymer having a preferred molecular weight can be appropriately polymerized in accordance with the relationship between the required physical properties and the intended use.
[0072] From the viewpoint of having a viscosity suitable for use in electronic materials, coatings, etc. and polymerizing in a practically acceptable time and cost, the weight average molecular weight (Mw) is preferably 250 to 2500. The weight average molecular weight (Mw) is more preferably 400 to 2000, and particularly preferably 500 to 1500.
[0073] The weight average molecular weight (Mw) of the allylamine (co)polymer can be measured by, for example, gel permeation chromatography (GPC method) using liquid chromatography.
[0074] The molecular weight of the allylamine (co)polymer can be appropriately adjusted by adjusting the presence, type and composition of the comonomer, the temperature, time and pressure in the polymerization step, the type and amount of the radical initiator used in the polymerization step, and the like.
[0075] The intrinsic viscosity [η] of the allylamine (co)polymer is not particularly limited and can be appropriately set in accordance with the relationship between the required physical properties and the intended use.
[0076] The viscosity of the allylamine (co)polymer can also be appropriately adjusted by adjusting the presence, type and composition of the comonomer, the temperature, time and pressure in the polymerization step, the type and amount of the radical initiator used in the polymerization step, and the like.
[0077] The proportion of the structural unit derived from allylamine in the allylamine (co)polymer is not particularly limited, but is preferably 10 to 100 mol %, more preferably 50 to 100 mol %.
[0078] When the ratio of the structural unit derived from allylamine is within the above range, preferred properties such as reactivity and dispersibility can be more easily achieved.
[0079] The composition of the allylamine (co)polymer represented by the ratio of the structural unit derived from allylamine can be appropriately adjusted by the polymerization conditions, in particular, the composition of the monomers supplied during the polymerization.
[0080] Method for producing allylamine (co)polymer
[0081] A method for producing an allylamine (co)polymer as another embodiment of the present invention comprises:
[0082] a) polymerizing the allylamine monomer to obtain an allylamine (co)polymer,
[0083] b) a step of decomposing the sulfuric acid groups in the obtained allylamine (co)polymer, and
[0084] c) A step of removing sulfur compounds generated by decomposition of sulfuric acid groups.
[0085] The method for producing the allylamine (co)polymer is particularly suitable for producing the allylamine (co)polymer of the present invention.
[0086] In addition, in step b) of the method for producing the allylamine (co)polymer, the amount of sulfate groups in the allylamine (co)polymer is preferably reduced to less than 20,000 mass ppm, more preferably to less than 18,000 mass ppm, and particularly preferably to less than 15,000 mass ppm, relative to the total mass of the allylamine (co)polymer.
[0087] a) Process of polymerizing allylamine monomer to obtain allylamine (co)polymer In the step a) of polymerizing the allylamine monomer to obtain the allylamine (co)polymer in the above production method, allylamine and a comonomer used as required are polymerized in water or a polar solvent. Here, the so-called allylamine includes both allylamine and its addition salt.
[0088] The addition salt of allylamine preferably used as the raw material monomer is usually an inorganic acid salt of allylamine. As such an inorganic acid salt of allylamine, for example, hydrochloride, sulfate, phosphate, perchlorate, nitrate, etc. of allylamine can be listed, but it is not limited to these. In addition, organic acid salts such as acetate can also be used.
[0089] As the polymerization medium, water or a polar solvent is used. Examples of the polar solvent include, but are not limited to, inorganic acids such as hydrochloric acid, sulfuric acid, phosphoric acid, and polyphosphoric acid or their aqueous solutions, organic acids such as formic acid, acetic acid, propionic acid, and lactic acid or their aqueous solutions, alcohols, dimethyl sulfoxide, dimethylformamide, and aqueous solutions of inorganic salts such as zinc chloride, calcium chloride, and magnesium chloride.
[0090] The addition salt of allylamine is generally used in the form of isolated crystals, but allylamine and an acid can also be added to the above-mentioned water or polar solvent to form an addition salt in this system. When an acid or its aqueous solution is used as the polymerization medium, a predetermined amount of allylamine can be added to the acid or its aqueous solution to directly polymerize it.
[0091] The concentration of allylamine in the polymerization medium during polymerization is not particularly limited, and is appropriately selected according to the type of the polymerization initiator used. For example, when using a peroxide-based free radical polymerization initiator, the monomer concentration is generally 10 to 80% by mass, preferably 20 to 70% by mass. If the allylamine concentration is low, low-molecular-weight allylamine (co)polymers are easily obtained, but the polymerization rate is easily reduced. On the contrary, if the allylamine concentration is too high, the polymerization rate is high, but the molecular weight of the allylamine (co)polymer is easily increased.
[0092] As the radical polymerization initiator used for polymerizing under low polymerization degree conditions, known peroxide radical polymerization initiators, radical polymerization initiators having an azo group and a cationic nitrogen-containing group, etc. can be used. Examples of the peroxide radical polymerization initiator include ammonium persulfate, sodium persulfate, potassium persulfate, etc., and peroxide radical polymerization initiators are particularly preferred from the perspectives of lowering the molecular weight of the allylamine polymer and improving the polymerization rate.
[0093] The radical polymerization initiator can be used alone or in combination of two or more thereof. In addition, it is necessary to use an amount greater than that used in a conventional polymerization reaction, usually 1.5% by mass or more, preferably 5 to 75% by mass, and more preferably 10 to 50% by mass relative to the addition salt of allylamine. Generally, if the amount of the radical polymerization initiator used is small, the polymerization rate decreases and the molecular weight tends to increase, which is not preferred.
[0094] When the addition salt of allylamine is polymerized in water or a polar solvent under low polymerization degree conditions, the polymerization can be carried out by lowering the monomer concentration of the polymerization system and raising the polymerization temperature. Furthermore, the polymerization yield can be increased by raising the concentration of the radical initiator.
[0095] b) Step of decomposing the sulfuric acid groups in the obtained allylamine (co)polymer
[0096] In the step b) of decomposing the sulfate groups in the obtained allylamine (co)polymer in the above production method, the sulfate groups bonded to the structure of the allylamine (co)polymer obtained in the above step a) are decomposed by heating or the like.
[0097] When decomposition is performed by heating, the obtained allylamine (co)polymer is preferably heated in the state of an aqueous solution at a temperature of 70° C. or higher for 12 hours or more.
[0098] In step b), the amount of sulfate groups in the allylamine (co)polymer is preferably reduced to less than 20,000 mass ppm, more preferably less than 18,000 mass ppm, and particularly preferably less than 15,000 mass ppm, relative to the total mass of the allylamine (co)polymer.
[0099] Furthermore, when the allylamine (co)polymer is present in the state of an addition salt in the polymerization solution after the completion of the polymerization, the above-mentioned polymerization solution can be subjected to a neutralization treatment with an alkali between step a) and step b), or between step b) and step c). The neutralization treatment can be carried out to such an extent that the addition salt of the allylamine (co)polymer becomes a free state, that is, the pH of the polymerization solution after neutralization is generally in the range of 9 to 13.5, preferably in the range of 10 to 13. There is no particular limitation on the alkali used in the neutralization treatment, and for example, alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferably listed. Through the neutralization treatment, the free acid reacts with the alkali to form a salt.
[0100] c) Step of removing sulfur compounds generated by decomposition of sulfuric acid groups
[0101] The solution after step b) contains unreacted allylamine and sulfur compounds generated by decomposition of the sulfuric acid group. Therefore, in step c), the sulfur compounds are removed together with the unreacted monoallylamine by distillation or the like.
[0102] In the distillation treatment, distillation is preferably carried out under reduced pressure, more preferably at a temperature of 40 to 100° C. and a vacuum degree of 10 to 300 mmHg, and particularly preferably at a temperature of 50 to 80° C. and a vacuum degree of 20 to 200 mmHg. Under such conditions, the allylamine (co)polymer is not distilled off but remains.
[0103] In the method of the embodiment of the present invention, the residual liquid after the unreacted monoallylamine is distilled off can be subjected to electrodialysis. (Alternatively, electrodialysis can be performed instead of distillation.) When the unreacted allylamine is distilled off, solvents such as water are also partially distilled off, so electrodialysis can be performed after dilution with a solvent. The electrodialysis preferably uses an ion exchange membrane.
[0104] In the present embodiment, the electrodialysis treatment using the ion exchange membrane is preferably performed under conditions such that the target allylamine (co)polymer is hardly removed but remains and the sulfur compound can be removed together with the unreacted monoallylamine.
[0105] use
[0106] The allylamine (co)polymer of the present invention achieves significant technical effects that exceed the limits of the prior art, such as reducing coloration and impurities to extremely low levels and being able to maintain these preferred properties for a long time. It can be suitably used in various applications requiring low coloration and low pollution, represented by electrical and electronic materials, papermaking treatment agents, inks, coatings, adhesives, display materials, and light-transmitting materials.
[0107] For example, the ink composition using the allylamine (co)polymer of the present invention has excellent water resistance, suppresses discoloration and aggregation, and also has excellent storage stability.
[0108] Example
[0109] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is by no means limited thereto.
[0110] In the following Examples and Comparative Examples, physical properties and characteristics were evaluated by the following methods.
[0111] (Weight average molecular weight of polymer)
[0112] The weight average molecular weight (Mw) of the polymer was measured by gel permeation chromatography (GPC method) using Chromaster (registered trademark) 5450 high-speed liquid chromatograph manufactured by Hitachi High-Tech Science & Technology Co., Ltd.
[0113] The detector used was an RI differential refractive index detector, and the column used a product formed by connecting the aqueous gel filtration type GS-220HQ (exclusion limit molecular weight 3000) and GS-620HQ (exclusion limit molecular weight 2 million) of the ショーデックスアサヒパック in series. For the sample, the concentration was adjusted to 0.5g / 100ml with the eluent, and 20μL was used. For the eluent, a 0.4mol / L sodium chloride aqueous solution was used. The column temperature was 30°C and the flow rate was 1.0ml / min.
[0114] As standard substances, polyethylene glycols having molecular weights of 106, 194, 440, 600, 1470, 4100, 7100, 10300, 12600, 23000, etc. were used to obtain a calibration curve, and the weight average molecular weight (Mw) of the polymer was obtained based on the calibration curve.
[0115] (Polymerization yield of polymer)
[0116] It was determined from the peak area ratio in a chart obtained by the GPC method.
[0117] (Ratio of sulfate groups in polymer)
[0118] Ion exchange water was appropriately added to the aqueous solution of the allylamine (co)polymer to adjust its concentration to about 10% by mass and the pH to about 11. The sulfur concentration was measured by ion chromatography with a combustion device using the solution. The ratio of sulfate groups in the polymer (mass basis) was calculated from the obtained sulfur concentration, the amount of the solution, and the concentration of the allylamine (co)polymer in the solution.
[0119] (Initial absorbance A 510 )
[0120] Ion exchange water was appropriately added to the aqueous solution of the allylamine (co)polymer to adjust the concentration to about 10% by mass and the pH to about 11. The solution was injected into a cell with an optical path length of 10 mm, and the absorbance at a wavelength of 510 nm was measured using a spectrophotometer manufactured by Hitachi Hitech Science (product name: UH5300), which was set as the initial absorbance A. 510 .
[0121] (Absorbance after time change A' 510 )
[0122] The initial absorbance A was collected in a 20 ml glass sample bottle. 510 The solution adjusted for the measurement was stored in a 70°C thermostat under accelerated conditions for 2 days. 510 The absorbance at a wavelength of 510 nm was measured in the same manner and the absorbance after time change was defined as A' 510 .
[0123] (Example 1)
[0124] In a 1L four-necked flask equipped with a stirrer, a thermometer and a condenser, 322.18g of an aqueous solution of allylamine hydrochloride with a concentration of 58.08% by mass was placed and the temperature was raised to 50°C. An aqueous initiator solution consisting of 35.24g of sodium persulfate and 65.44g of water was dripped at an internal temperature of 48°C to initiate polymerization. The aqueous initiator solution was dripped over 3 hours while the internal temperature was maintained at 50-55°C. The polymerization was further continued for 1 hour, and the polymerization was allowed to proceed for a total of 4 hours, thereby obtaining a light yellow aqueous solution of allylamine hydrochloride with a GPC yield of 63.27% and a weight average molecular weight Mw of 1016.
[0125] Then, the temperature was raised to 70°C and the sulfuric acid group was thermally decomposed for 96 hours to obtain an orange solution. 368 g of sodium hydroxide with a concentration of 25% by mass was added under cooling below 30°C, mixed and neutralized. 729.69 g of the aqueous solution of the allylamine polymer with an allylamine concentration of 14.49% by mass was distilled under a reduced pressure of 30 mmHg at 50°C until it became 429.18 g, and unreacted allylamine was distilled off. Then, by diluting with water, 880.47 g of an aqueous solution of the allylamine polymer with a concentration of 9.95% by mass was obtained. The aqueous solution was subjected to electrodialysis using an ion exchange membrane (as a dialysis apparatus, CH-0 type manufactured by Nippon Rensui Co., Ltd. was used. As a cation exchange membrane, 8 sheets of CMV manufactured by Asahi Glass Co., Ltd. were used, and as anion exchange membrane, 5 sheets of AMV manufactured by Asahi Glass Co., Ltd. were used. 1L of 1 mass % aqueous sodium chloride solution was loaded into the concentrate tank, and 1L of 1 mass % aqueous sodium sulfate solution was loaded into the pole liquid tank.). A maximum DC voltage of 5A or 13.5V was applied between the electrodes, and the treatment was carried out for 4 hours under this condition.
[0126] Ion exchange water was added to the treated solution to obtain 689.40 g of a yellow aqueous solution having a concentration of 10.22 mass %, a pH of 11.64, and a weight average molecular weight Mw of 952. The sulfate group concentration was measured using this solution and found to be 13665 mass ppm based on the mass of the allylamine polymer.
[0127] The initial absorbance A of the solution at a wavelength of 510 nm was measured. 510 The absorbance A' at a wavelength of 510 nm after the same solution was treated at 70°C for 2 days was 0.059. 510 =0.075. That is, the change in absorbance at a wavelength of 510 nm caused by keeping it at 70°C for 2 days is A' 510 / A 510 It is 1.271.
[0128] Table 1 shows the results.
[0129] (Example 2)
[0130] In a 1L four-necked flask equipped with a stirrer, a thermometer and a condenser, 318.29g of an aqueous solution of allylamine hydrochloride having a concentration of 58.79% by mass was placed and the temperature was raised to 50°C. An aqueous initiator solution consisting of 33.68g of ammonium persulfate and 62.55g of water was dripped at an internal temperature of 49°C to initiate polymerization. The aqueous initiator solution was dripped over a period of 3 hours while the internal temperature was maintained at 50-55°C. The polymerization was further continued for 1 hour, and the polymerization was allowed to proceed for a total of 4 hours, thereby obtaining a light yellow aqueous solution of allylamine hydrochloride polymer having a GPC yield of 53.40% and Mw of 1143.
[0131] Then, the temperature was raised to 70°C and the sulfuric acid group was thermally decomposed for 48 hours to obtain an orange solution. 416.00 g of sodium hydroxide with a concentration of 25% by mass was added under cooling below 30°C, mixed and neutralized. 798.48 g of the aqueous solution of the allylamine polymer with an allylamine concentration of 14.89% by mass was distilled under a reduced pressure of 30 mmHg at 50°C until it became 397.19 g, and unreacted allylamine was distilled off. Then, by diluting with water, 841.40 g of an aqueous solution of the allylamine polymer with a concentration of 10.01% by mass was obtained. The aqueous solution was subjected to electrodialysis using an ion exchange membrane (as a dialysis apparatus, CH-0 type manufactured by Nippon Rensui Co., Ltd. was used. As a cation exchange membrane, 8 sheets of CMV manufactured by Asahi Glass Co., Ltd. were used, and as anion exchange membrane, 5 sheets of AMV manufactured by Asahi Glass Co., Ltd. were used. 1L of 1 mass % aqueous sodium chloride solution was loaded into the concentrate tank, and 1L of 1 mass % aqueous sodium sulfate solution was loaded into the pole liquid tank.). A maximum DC voltage of 5A or 13.5V was applied between the electrodes, and the treatment was carried out for 4 hours under this condition.
[0132] Ion exchange water was added to the treated solution to obtain 733.29 g of a yellow aqueous solution with a concentration of 10.33 mass %, pH of 11.41, and a weight average molecular weight of 872. Using this solution, the sulfur concentration in the aqueous solution was measured by ion chromatography with a combustion device, and the result was high, 1957 ppm. Therefore, electrodialysis treatment was performed again. A yellow aqueous solution with a concentration of 728.51 g of 9.68 mass %, pH of 11.34, and a weight average molecular weight of 957 was obtained. The sulfur concentration in the aqueous solution was measured, and the result was still high, 1611 ppm. Therefore, for 100 g of the aqueous solution, 30 mL of ion exchange resin (DIAION SA10AOH manufactured by Mitsubishi Chemical Corporation) that had been washed and dehydrated was added and stirred for 10 minutes. Then, it was allowed to stand for 50 minutes, and the ion exchange resin was filtered and separated to obtain 98.12 g of a yellow aqueous solution with a concentration of 8.94 mass %. The sulfate group concentration was measured and found to be 6456 ppm by mass based on the mass of the allylamine polymer.
[0133] The initial absorbance A of the solution at a wavelength of 510 nm was measured. 510 The absorbance A' at a wavelength of 510 nm after the same solution was treated at 70°C for 2 days was 0.037. 510 =0.049. That is, the change in absorbance at a wavelength of 510 nm caused by keeping it at 70°C for 2 days is A' 510 / A 510 is 1.324.
[0134] Table 1 shows the results.
[0135] (Example 3)
[0136] In a 1L four-necked flask equipped with a stirrer, a thermometer and a condenser, 322.40g of an aqueous solution of allylamine hydrochloride having a concentration of 58.04% by mass was placed and the temperature was raised to 50°C. An aqueous initiator solution consisting of 70.48g of sodium persulfate and 130.89g of water was dripped at an internal temperature of 49°C to initiate polymerization. The aqueous initiator solution was dripped over a period of 3 hours while the internal temperature was maintained at 50-55°C. The polymerization was further continued for 1 hour, and the polymerization was allowed to proceed for a total of 4 hours, thereby obtaining a light yellow aqueous solution of allylamine hydrochloride having a GPC yield of 74.19% and Mw of 892.
[0137] Then, the temperature was raised to 70°C and the sulfuric acid group was thermally decomposed for 48 hours to obtain a brown solution. 409.40 g of sodium hydroxide with a concentration of 25% by mass was added under cooling below 30°C, mixed and neutralized. 902.73 g of the aqueous solution of the allylamine polymer with an allylamine concentration of 11.58% by mass was distilled under a reduced pressure of 30 mmHg at 50°C until it became 422.94 g, and unreacted allylamine was distilled off. Then, by diluting with water, 1018.75 g of an aqueous solution of the allylamine polymer with a concentration of 9.64% by mass was obtained. The aqueous solution was subjected to electrodialysis using an ion exchange membrane (as a dialysis apparatus, CH-0 type manufactured by Nippon Rensui Co., Ltd. was used. As a cation exchange membrane, 8 sheets of CMV manufactured by Asahi Glass Co., Ltd. were used, and as anion exchange membrane, 5 sheets of AMV manufactured by Asahi Glass Co., Ltd. were used. 1L of 1 mass % sodium chloride aqueous solution was loaded into the concentrate tank, and 1L of 1 mass % sodium sulfate aqueous solution was loaded into the pole liquid tank.). A maximum DC voltage of 5A or 13.5V was applied between the electrodes, and the treatment was carried out for 10 hours under this condition.
[0138] Ion exchange water was added to the treated solution to obtain 789.80 g of a brown aqueous solution with a concentration of 10.20 mass%, pH of 11.08, and a weight average molecular weight of Mw of 791. Using this solution, the sulfur concentration in the aqueous solution was measured by ion chromatography with a combustion device, and the result was high, 3983 ppm. Therefore, electrodialysis treatment was performed again. A brown aqueous solution with a concentration of 773.06 g of 9.42 mass%, pH of 11.13, and a weight average molecular weight of Mw of 747 was obtained. The sulfur concentration in the aqueous solution was measured, and the result was still high, 2997 ppm. Therefore, for 100 g of the aqueous solution, 30 mL of ion exchange resin (DIAION SA10AOH manufactured by Mitsubishi Chemical Corporation) that had been washed and dehydrated was added and stirred for 10 minutes. Then, it was allowed to stand for 50 minutes, and the ion exchange resin was filtered and separated to obtain 98.62 g of a brown aqueous solution with a concentration of 7.66 mass%. The sulfate group concentration was measured and found to be 10663 ppm by mass based on the mass of the allylamine polymer.
[0139] The initial absorbance A of the solution at a wavelength of 510 nm was measured. 510 is 0.185. In addition, the absorbance A' at a wavelength of 510 nm after the same solution was treated under accelerated conditions at 70°C is 510 =0.241. That is, the change in absorbance at a wavelength of 510 nm caused by keeping it at 70°C for 2 days is A' 510 / A 510 It is 1.303.
[0140] Table 1 shows the results.
[0141] (Comparative Example 1)
[0142] In a 1L four-necked flask equipped with a stirrer, a thermometer and a condenser, 319.86g of an aqueous solution of allylamine hydrochloride having a concentration of 58.5% by mass was placed and the temperature was raised to 50°C. An aqueous initiator solution consisting of 35.24g of sodium persulfate and 65.44g of water was dripped at an internal temperature of 48°C to initiate polymerization. The aqueous initiator solution was dripped over a period of 3 hours while maintaining the internal temperature at 50-55°C. The polymerization was further continued for 1 hour, and the polymerization was allowed to proceed for a total of 4 hours, thereby obtaining a light yellow aqueous solution of allylamine hydrochloride having a GPC yield of 63.75% and a weight average molecular weight Mw of 1055.
[0143] Under cooling below 30°C, 368 g of sodium hydroxide with a concentration of 25% by mass was added, mixed, and neutralized. 782.66 g of the aqueous solution of the allylamine polymer with an allylamine concentration of 12.66% by mass was distilled at 50°C under a reduced pressure of 30 mmHg until it became 362.89 g, and unreacted allylamine was distilled off. Further, by diluting with water, 879.25 g of an aqueous solution of an allylamine polymer with a concentration of 6.54% by mass was obtained. The aqueous solution was electrodialyzed using an ion exchange membrane (as a dialysis device, CH-0 type manufactured by Nippon Reishi Co., Ltd. was used. As a cation exchange membrane, 8 sheets of CMV manufactured by Asahi Glass Co., Ltd. were used, and as an anion exchange membrane, 5 sheets of AMV manufactured by Asahi Glass Co., Ltd. were used. 1 L of a 1% by mass sodium chloride aqueous solution was placed in the concentrate tank, and 1 L of a 1% by mass sodium sulfate aqueous solution was placed in the pole liquid tank.). A maximum DC voltage of 5 A or 13.5 V was applied between the electrodes, and the treatment was performed for 4 hours under this condition.
[0144] Ion exchange water was added to the concentrated solution to obtain 482.47 g of a pale yellow aqueous solution having a concentration of 10.28 mass %, a pH of 11.44, and a weight average molecular weight Mw of 1013. The sulfate group concentration was measured using this solution and found to be 27466 mass ppm based on the mass of the allylamine polymer.
[0145] The initial absorbance A of the solution at a wavelength of 510 nm was measured. 510 The absorbance A' at a wavelength of 510 nm after the same solution was treated at 70°C for 2 days was 0.033. 510 =0.140. That is, the change in absorbance at a wavelength of 510 nm caused by keeping it at 70°C for 2 days is A' 510 / A 510 is 4.242.
[0146] Table 1 shows the results.
[0147] (Example 4)
[0148] The initial absorbance A at a wavelength of 510 nm was measured under the condition that the allylamine polymer aqueous solution with a concentration of 10.22 mass % and a pH of 11.64 prepared in Example 1 was adjusted to pH 7 with 35% hydrochloric acid. 510 The result is 0.081. In addition, the absorbance A' at a wavelength of 510nm after the same solution was treated under accelerated conditions of 70°C for 2 days 510 That is, when the pH is adjusted to 7, the change in absorbance at a wavelength of 510 nm caused by keeping it at 70°C for 2 days is A' 510 / A 510It is 2.074.
[0149] Table 1 shows the results.
[0150] (Comparative Example 2)
[0151] When the aqueous allylamine polymer solution prepared in Comparative Example 1 with a concentration of 10.28 mass % and a pH of 11.44 was adjusted to pH 7 with 35% hydrochloric acid, the initial absorbance A at a wavelength of 510 nm was 510 The absorbance A' at a wavelength of 510 nm after the same solution was treated at 70°C for 2 days was 510 =0.718. That is, when the pH is adjusted to 7, the change in absorbance at a wavelength of 510 nm caused by keeping it at 70°C for 2 days is A' 510 / A 510 is 13.055.
[0152] Table 1 shows the results.
[0153] [Table 1]
[0154]
[0155] Industrial Applicability
[0156] The allylamine (co)polymer of the present invention exceeds the limits of the prior art and achieves significant technical effects of high practical value, such as reducing coloration and impurities to extremely low levels and being able to maintain these preferred properties for a long time. It has high applicability in various fields of industries represented by the chemical industry, papermaking industry, and electrical and electronic industry.
[0157] The method of the present invention can efficiently produce allylamine (co)polymers having preferred properties, such as the above-mentioned allylamine (co)polymers, and therefore has high applicability in various fields of industry.
Claims
1. An allylamine polymer, which is a homopolymer composed of structural units derived from an allylamine monomer, wherein the weight average molecular weight of the allylamine polymer is 250 to 2500, and the allylamine polymer contains a sulfate group in the structure, and the proportion of the sulfate group relative to the total mass of the allylamine polymer is 13665 mass ppm or less, The structural unit derived from the allylamine monomer has a structure represented by the following formula (I):
2. The allylamine polymer according to claim 1, wherein The initial absorbance A at a wavelength of 510 nm measured for an aqueous solution of the allylamine polymer prepared to have a concentration of 10 mass % and a pH of 11 is 510 The absorbance A' at a wavelength of 510 nm after the aqueous solution was kept at 70°C for 2 days was 0.5 or less. 510 and initial absorbance A 510 Ratio A' 510 / A 510 Is 3 or less.
3. A paper processing agent, ink, coating or adhesive, comprising the allylamine polymer according to claim 1 or 2.
4. An electric and electronic material or a display material comprising the allylamine polymer according to claim 1 or 2.
5. A light-transmitting material comprising the allylamine polymer according to claim 1 or 2.
Citation Information
Patent Citations
Preparation of polymer of monoallylamine
JP1983201811A
Production of low-molecular-weight polymer of monoallylamine hydrochloride
JP1987172007A
Setting agent for substantive dye
JP1993195450A
Process for producing low-molecular-weight allylamine polymers or addition salts thereof
WO1999019372A1
Preparation of copolymer of allyl amide and allyl alcohol
JP2000281728A